(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Through the article, it is possible to have theoretical aspects of the organization of psychological service in a special educational institution, tasks that need to be solved by psychologist R.S. Nemov within the framework of educational psychological service, opinions about the personality of a psychologist in the organization of a psychological service in a special educational institution .